Inter-Rater Reliability of Pain Provocation Tests for Painful Lumbar Facet Joints. A Pilot Study - Thalhamer, Christoph; Hahne, Julia; Matthijs, Omer; Machacek, Peter (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background With a life-time prevalence of 39%, low back pain (LBP) is one of the most common musculoskeletal disorders. Correct diagnosis of underlying causes is commonly seen as a prerequisite for successful therapy of LBP. Currently, there is no useful, non-invasive clinical test to diagnose painful lumbar zygapophyseal joints. Clinical tests with high diagnostic accuracy are therefore desirable. Inter-rater reliability is commonly seen as a prerequisite of test validity. The objective of this pilot study was thus to evaluate inter-rater reliability of new clinical pain provocation tests for diagnosing painful lumbar zygapophyseal joints. If a clinically significant level of inter-rater reliability were to be determined, this study could constitute a first step towards establishing the clinical utility of this new set of tests in the structural diagnosis of low back disorders.Material and Methods Patients participating in this study were recruited in a specialist hospital throughout June 2015 until September 2016. Both female and male patients with current LBP, with or without buttock or lower extremity symptoms were screened for inclusion. Patients had preferably to be 50 years or older in order to be included in this study. The upper age limit was set at 90 years. They also had to be fluent in German to be able to follow verbal instructions. Exclusion criteria comprised the presence of red flags, surgical spinal fusion at any level of the lumbar spine, discectomy within the past 12 months, radiculopathy and/or radicular pain, interventional treatments for the IVD, SIJs or ZAJs within the past three months, psychiatric disorders, current litigation issues concerning back pain, and central nervous system diseases. Three certified manual therapy instructors tested patients independently. Fleissʼ kappa values and percent agreements were calculated.Results Subjects included a sample of 48 patients (15 males and 33 females) with a mean age of 66.48 years (range 33 – 90) presenting at a specialist hospital with low back pain. The new pain provocation tests for lumbar zygapophyseal joints showed moderate reliability (Fleissʼ κ = 0.46) and an overall percent agreement of 68.8%. Separate tests for the zygapophyseal joints of L5–S1 showed fair reliability (Fleissʼ κ = 0.37) and an overall percent agreement of 64.6%. Unidimensional tests that were used in the study to exclude the intervertebral disc as a nociceptive generator showed fair reliability as well (average κ of 0.28 and 0.39, respectively). Neither drop outs nor adverse events occurred.Conclusion The new pain provocation tests for lumbar zygapophyseal joints showed clinically significant levels of inter-rater reliability. Validation of these tests against fluoroscopy-guided medial branch blocks is warranted.
Keywords: agreement; low back pain; reliability; structural diagnosis; facet joint